1996
DOI: 10.1002/anie.199615271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Surrounding Medium on the Interaction of Nitriles with Boron Trifluoride

Abstract: The remarkable change in the BN bond lengths of CH3CN · BF3 and HCN · BF3 between the gas phase and the condensed phase has been attributed to effects of the surrounding medium. Results herein suggest that in BF3‐rich argon matrices, CH3CN · BF3 and HCN · BF3 are present in the form with a short BN bond, as is CH3CN · BF3 in solution in benzene. The two structural alternatives for HCN · BF3 are shown schematically above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 27 publications
(2 reference statements)
5
31
3
Order By: Relevance
“…Benzonitrile (BN) also binds to LP in DE. The C⋮N stretching mode for BN at 2228 cm -1 is systematically replaced by a new C⋮N mode at higher energy (∼2255 cm -1 ) as the concentration of LP in DE is increased. This new mode arises from the BN·LP adduct .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzonitrile (BN) also binds to LP in DE. The C⋮N stretching mode for BN at 2228 cm -1 is systematically replaced by a new C⋮N mode at higher energy (∼2255 cm -1 ) as the concentration of LP in DE is increased. This new mode arises from the BN·LP adduct .…”
Section: Resultsmentioning
confidence: 99%
“…The C⋮N stretching mode for BN at 2228 cm -1 is systematically replaced by a new C⋮N mode at higher energy (∼2255 cm -1 ) as the concentration of LP in DE is increased. This new mode arises from the BN·LP adduct . Unlike the CO mode for CA in LP/DE, the C⋮N mode for BN does not change position and minimally changes line width in LP/DE (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…33 A trivalent triel atom in TrR 3 , owing to its electron deciency, is usually used to bind with Lewis bases such as HCN, CH 3 CN, and NH 3 . [34][35][36][37][38][39][40][41] Upon complexation, the geometric structure of TrR 3 exhibits substantial deviation from the planar one, and it becomes more prominent for a stronger triel bond. There is clear difference between the solid-and gas-phase structures of HCN/BF 3 , which is mainly caused by the cooperative effect in the solid.…”
Section: Introductionmentioning
confidence: 99%
“…From another direction, it has been demonstrated that BR 3 (R = H or halogen) can bind strongly to Lewis bases such as HCN, CH 3 CN, and NH 3 . The strength of this bonding has been attributed in a large part to the electron deficiency of a trivalent triel atom, making it a strong Lewis acid.…”
Section: Introductionmentioning
confidence: 99%
“…From another direction, it has been demonstrated that BR 3 (R = H or halogen) can bind strongly to Lewis bases such as HCN, CH 3 CN, and NH 3 . [21][22][23][24][25][26][27][28][29] The strength of this bonding has been attributed in a large part to the electron deficiency of a trivalent triel atom, making it a strong Lewis acid. Another property evoking interest in such complexes is their unusually large differences in gas and solid structures.…”
mentioning
confidence: 99%